Academic authenticity of neuro-linguistic programming as a discursive practice - Yu. V. Gilyasev (Дискурс профессиональной коммуникации, 2019)
Neuro-linguistic programming (NLP) is considered to be one of the socially valued practices whose conceptual and methodological grounds can be articulated when seen in the light of its discursive representation. Characterization and evaluation of this area in applied psychology proceeds through analysis of expert standpoints and views rendered in secondary sources where they express the conformity level of the discourse in question to academic standards existent in psychology as a theory. Special attention is given to the propositional expression of the ideas defining NLP studies as well as to the exposure of presuppositional attitudes of the NLP expert whose textbook is under discussion in the article. The logical correctness and validity of those presuppositions are analyzed in relation to their adequate representation of scientific or mass worldview. After having exposed the author’s intentions one can state the pragmatic strategy and ideology pursued by the NLP expert in the textbook alongside with the identity of NLP as a discursive and social practice, its position among other discursive practices. The results obtained after the analysis of a particular piece of NLP discourse are congruent with the current trends typical of postmodernist consumerist society. Characteristic postmodernist ways to organize verbal interaction – in particular, forms of discourse imitation, its variation and hybridization – are found in the examples provided. A practical workbook on NLP in English was taken as a source for evidence. Critical discourse-analysis (CDA) served as the guiding approach to the problem, which was realized at some points of the study as contextual analysis, definitive analysis, interpretation method, statistical procedures altogether with quantitative estimation.